Mountain roads shift native and non-native plant species' ranges - Lembrechts, Jonas (2017)
Roads are known to act as corridors for dispersal of plant species. With their variable microclimate, role as corridors for species movement and reoccurring disturbance events, they show several characteristics that might influence range dynamics of both native and non-native species. Previous research on plant species ranges in mountains however seldom included the effects of roads. To study how ranges of native and non-native species differ between roads and adjacent vegetation, we used a global dataset of plant species composition along mountain roads. We compared average elevation and range width of species, and used generalized linear mixed models (GLMMs) to compile their range optimum and amplitude. We then explored differences between roadside and adjacent plots based on a species? origin (native vs non-native) and nitrogen and temperature affinity. Most non-native species had on average higher elevational ranges and broader amplitudes in roadsides. Higher optima for non-native species were associated with high nitrogen and temperature affinity. While lowland native species showed patterns comparable to those in non-native species, highland native species had significantly lower elevational ranges in roadsides compared to the adjacent vegetation. We conclude that roadsides indeed change the elevational ranges of a variety of species. These changes are not limited to the expansion of non-native species along mountain roads, but also include both upward and downward changes in ranges of native species. Roadsides may thus facilitate upward range shifts, for instance related to climate change, and they could serve as corridors to facilitate migration of alpine species between adjacent high-elevation areas. We recommend including the effects of mountain roads in species distribution models to fine-tune the predictions of range changes in a warming climate.